k = 1 ∑ ∞ k sin k = c π a − b
If the equation above holds true for positive integers a , b and c , find a + b + c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How did you get from line 5 to 6?
Log in to reply
I have added two lines to explain. Hope that it helps.
It is not hard to observe that the series given is actually the Fourier series expansion of the function f ( x ) = 2 π − x for x ∈ ( 0 , 2 π ) in disguise, i.e. k = 1 ∑ ∞ k sin k x = 2 π − x . Substituting x = 1 yields the final result.
let I= ∑ k = 1 ∞ k sin ( k )
I= ∑ k = 1 ∞ k I m { e i k }
I= I m { ∑ k = 1 ∞ k e i k } = I m { ∑ k = 1 ∞ k ( e i ) k }
I= I m { − ln ( 1 − e i ) }
let z= 1 − e i = ( 1 − cos ( 1 ) ) + i ( − sin ( 1 ) )
I= m { − ln ( z ) }
I= I m { − ( ln ( ∣ z ∣ ) + i θ ) } * \\ definition of logarithm in complex *
I= − θ = − tan − 1 ( 1 − cos ( 1 ) − sin ( 1 ) ) = tan − 1 ( 1 − cos ( 1 ) sin ( 1 ) )
Now
1 − cos ( 1 ) = 2 ⋅ 2 1 − cos ( 2 ⋅ 2 1 ) = 2 sin 2 ( 2 1 ) * \\ since sin 2 ( x ) = 2 1 − cos ( 2 x ) *
and
sin ( 1 ) = sin ( 2 ⋅ 2 1 ) = 2 sin ( 2 1 ) cos ( 2 1 )
so I= tan − 1 ( 2 sin 2 ( 2 1 ) 2 sin ( 2 1 ) cos ( 2 1 ) )
I= tan − 1 ( cot ( 2 1 ) )
I= tan − 1 ( tan ( 2 π − 2 1 ) )
I= 2 π 1 − 1
a=1,b=1 and c=2
a+b+c=4
Problem Loading...
Note Loading...
Set Loading...
Similar solution with @Hassan Abdulla's
S = k = 1 ∑ ∞ k sin k = k = 1 ∑ ∞ k ℑ ( e i k ) = ℑ ( k = 1 ∑ ∞ k e i k ) = ℑ ( − ln ( 1 − e i ) ) = ℑ ( − ln ( 1 − cos 1 − i sin 1 ) ) = ℑ ⎝ ⎛ − ln ⎝ ⎛ ( 1 − cos 1 ) 2 + sin 2 1 ⎝ ⎛ ( 1 − cos 1 ) 2 + sin 2 1 1 − cos 1 − i sin 1 ⎠ ⎞ ⎠ ⎞ ⎠ ⎞ = ℑ ( − ln ( 2 − 2 cos 1 ( 2 − 2 cos 1 1 − cos 1 + i 2 − 2 cos 1 − sin 1 ) ) ) = ℑ ( − ln ( 2 − 2 cos 1 exp ( i tan − 1 1 − cos 1 − sin 1 ) ) ) = ℑ ( − ln ( 2 − 2 cos 1 ) − ln ( exp ( i tan − 1 1 − cos 1 sin 1 ) ) ) = ℑ ( − ln ( 2 − 2 cos 1 ) + i tan − 1 1 − cos 1 sin 1 ) = tan − 1 1 − cos 1 sin 1 = tan − 1 1 − 1 + t 2 1 − t 2 1 + t 2 2 t = tan − 1 t 1 = tan − 1 tan 2 1 1 = tan − 1 cot 2 1 = 2 π − tan − 1 tan 2 1 = 2 π − 1 By Euler’s formula e i θ = cos θ + i sin θ where ℑ ( z ) is the imaginary part of z . By Maclaurin series ln ( 1 − x ) = − n = 1 ∑ ∞ n x n By Euler’s formula where exp ( x ) = e x Using half-angle tangent substitution and let t = tan 2 1
⟹ a + b + c = 1 + 1 + 2 = 4